2016
DOI: 10.1073/pnas.1604479113
|View full text |Cite
|
Sign up to set email alerts
|

Highly variable individual donor cell fates characterize robust horizontal gene transfer of an integrative and conjugative element

Abstract: Horizontal gene transfer is an important evolutionary mechanism for bacterial adaptation. However, given the typical low transfer frequencies in a bacterial population, little is known about the fate and interplay of donor cells and the mobilized DNA during transfer. Here we study transfer of an integrative and conjugative element (ICE) among individual live bacterial cells. ICEs are widely distributed mobile DNA elements that are different than plasmids because they reside silent in the host chromosome and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
106
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(112 citation statements)
references
References 47 publications
(93 reference statements)
4
106
1
Order By: Relevance
“…For example, when activated, ICEclc, an ICE active in Pseudomonas species, can inhibit host cell growth (ϳ50% of activated cells stop dividing) and cause cell lysis (77,82). Despite the damage incurred by host cells, 75% of donors with excised ICEclc that contact a recipient cell successfully transfer the element (82). Single-cell microscopy studies, such as those conducted on ICEclc, are required to assess the effect of Tn916 induction on host cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…For example, when activated, ICEclc, an ICE active in Pseudomonas species, can inhibit host cell growth (ϳ50% of activated cells stop dividing) and cause cell lysis (77,82). Despite the damage incurred by host cells, 75% of donors with excised ICEclc that contact a recipient cell successfully transfer the element (82). Single-cell microscopy studies, such as those conducted on ICEclc, are required to assess the effect of Tn916 induction on host cell fate.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experimental data suggested that the tc cells indeed do not return to a silent ICE clc state, but become irreparably damaged, arrest their division and wither [13]. However, because their number is proportionally low, there is no fitness cost on the population carrying the ICE [48,49]. The advantage of prolonged feedback loop output is that constant levels of the BisCD regulator can be maintained, allowing coordinated and organized production of the components necessary for the ICE clc transfer itself.…”
Section: Discussionmentioning
confidence: 99%
“…Up to ten images at different positions were acquired using Visiview software (Visitron systems GMbH), with exposures set to 40 ms, 500 ms and 500 ms for phase contrast (PhC), eGFP and eCherry, respectively. Cells were automatically segmented on image sets using pipelines described previously [12,48], from which their fluorescence (either eGFP or eCherry, or both) was quantified. Subpopulations of transfer competent cells were quantified using quantile-quantile-plotting as described previously [12,65].…”
Section: Methodsmentioning
confidence: 99%
“…[19] In this case they used clever tricks to indirectly visualize the excision, transfer and re-integration of a mobile genetic element from the chromosome of a donor cell into the chromosome of a recipient cell. By tracing each cell's history by imaging the transfer of the genetic element, they define the donor cell by reduced cell division rates or growth arrest, persistence, or lysis after the transfer has started.…”
Section: Virologymentioning
confidence: 99%